The Role of Customs Administrations in Preparation of Regional Integration in the European Union - Carsten Weerth (Global Trade and Customs Journal, 2010)
The national customs services of the twenty-seven EU Member States are playing a crucial role for the preparation of the admission of further states to the European Union (EU) by helping to build structures and teach the EU Customs Law in order to enable candidate states to apply the acquis communautaire. The so-called `twinning' is an important and practical approach to facilitate the transfer of knowledge about EU Customs Law to candidate countries. This article explains the legal basis and also shows the practical limitations and problems of the twinning projects in EU Customs Law. It also shows the benefits of the new EU Customs Blueprints for a uniform capacity building of candidate countries.
Additional information: Self-archiving of author's post-print (accepted paper) for scientific use only on personal page in RePec (e.g. https://authors.repec.org) according to publishers policies as documented on SHERPA/ROMEO database under URL: http://www.sherpa.ac.uk/romeo/issn/1569-755X/en//. Copyright-holder is Kluwer Law International.
Keywords: K33; K34; F53; 330; Customs Law; EU Enlargement; Capacity Building; European Union; Europan Law; Regional Integration